Inted: an intelligent tool for designing highly effective instructional environments - Sierra, Enrique Ariel (2002)
Instruction may be seen as the intentional creation of conditions around learning so as to facilitate the achievement of determined goals. Normally, instruction is based upon certain educational strategies. It is well accepted in the field of educational technology that these strategies should be founded on a theoretical framework. However, the adoption of epistemological perspectives for instructional design is not enough. It would also be useful to count on the knowledge and experience of qualified instructional designers. The expert system introduced in this paper, called INTED, tries to capture the knowledge of instructional designers and so it is capable of recommending suitable strategies that facilitate the design of learning environments. For that purpose, the system developed is based upon a pattern of instruction which synthesizes theories, research results and experience in order to converge towards the accomplishment of an instructional design which will be highly effective in terms of achievement of its educational goals.